Nefropatía diabética: diagnóstico y tratamiento - Ambuludi Farez, Cristhian Eduardo (Machala : Universidad Técnica de Machala, 2023)
Introduction: Diabetic nephropathy is one of the main complications of type 2 diabetes mellitus, affecting the patient's quality of life. Chronic hyperglycemia and arterial hypertension are conditions that are involved in the pathogenesis of the anatomical damage of the nephrons, first affecting the nephron's mensagium and then the damage becomes more diffuse, which is related to the clinical stages of Mogensen and over the years manifests as end-stage renal failure. The earliest indicator of renal damage in diabetic patients is microalbuminuria and at this stage more emphasis should be placed on practicing dietary interventions, adequate glucose control, blood pressure levels at therapeutic goals and the use of various drugs which help prevent the development or progression of renal injury. Objective: to analyze the diagnostic approach and adequate treatment in the deterioration of renal function due to diabetes mellitus by reviewing updated scientific articles. Methodology: this is a descriptive, non-experimental, cross-sectional, descriptive study by analyzing the clinical history. Conclusions: innovative treatments such as SGLT2, GLP-1 agonist, Finerenone, have solid evidence of helping to reduce cardiovascular risks, reduce the development of diabetic nephropathy and slow its evolution towards end-stage renal disease.
Introducción: la nefropatía diabética es una de las complicaciones primordiales de la diabetes mellitus tipo 2, afectando a la calidad de vida del paciente. La hiperglicemia crónica e hipertensión arterial son condiciones que están involucradas en la patogenia del daño anatómico de las nefronas afectando en primera instancia el mesangio de la nefrona para luego tornarse el daño de manera más difusa, la cual se relaciona con las etapas clínicas de Mogensen y que a lo largo de los años se manifiesta como insuficiencia renal terminal. El indicador de daño renal más precoz en los pacientes diabéticos es la microalbuminuria y en esta etapa se debe hacer más énfasis en practicar las intervenciones dietéticas, control adecuada de la glucosa, niveles de presión arterial en metas terapéuticas y la utilización de diversos fármacos los cuales ayudan a prevenir el desarrollo o la progresión de la injuria renal. Objetivo: analizar el abordaje diagnóstico y el adecuado tratamiento en el deterioro de la función renal a causa de la diabetes mellitus mediante la revisión de artículos científicos actualizados. Metodología: se trata de un estudio tipo descriptivo no experimental de corte transversal, mediante el análisis de la historia clínica. Conclusiones: los tratamientos innovadores como los SGLT2, agonista GLP-1, Finerenona, tienen evidencia sólida de ayudar a disminuir los riesgos cardiovasculares, reducir el desarrollo de la nefropatía diabética y enlentecer su evolución hacia una enfermedad renal terminal.
Keywords: NEFROPATIA TERMINA; TASA DE FILTRACION GLOMERULAR; ALBUMINURIA; DIABETES MELLITUS